Learning from success and failure : implications for entrepreneurs, SMEs, and policy - Lafuente, Esteban; Rabetino, Rodrigo; Leiva, Juan Carlos (Springer Science+Business Media, 2024)
Despite the valuable contributions of earlier learning studies, the specific analysis of how entrepreneurs and small- and medium-sized enterprises (SMEs) learn has been sidelined in the literature. Significant research opportunities remain open in various unexplored realms. By adopting a multidisciplinary perspective that combines a variety of frameworks (i.e., organizational, economic, and innovation management), the collection of 11 studies of this special issue dedicated to learning delivers valuable insights into how entrepreneurs and SMEs capitalize on learning processes, while identifying how these processes are affected by the type of experience (i.e., success and failure). This paper first overviews the contributions of the 11 papers included in the special issue. Next, we discuss a number of yet unresolved topics that deserve academic attention, paying special attention to entrepreneurs’ direct and indirect experiences, knowledge obsolescence caused by technology upgrading, and the role of digital technologies—i.e., Internet-of-things and artificial intelligence—in the learning processes.
Keywords: Learning from success; Learning from failure; SMEs; learning; small and medium-sized enterprises; entrepreneurship; fi=Strateginen johtaminen|en=Strategic Management|